Stable isotopes confirm the Banwell Bone Cave Mammal Assemblage Zone represents an MIS 5 fauna. (May 2021) - Stevens, Rhiannon E.; Reade, Hazel
Abstract: The position of the Banwell Bone Cave mammal assemblage zone (MAZ) in the mammalian biostratigraphy of the British Isles has been the focus of debate for decades. Dominated by fauna typical of cold environments it was originally linked to the marine oxygen isotope stage (MIS) 4 stadial (ca. 72–59 ka). Subsequently it was argued that the Banwell Bone Cave MAZ more likely relates to the temperate interstadial of MIS 5a (ca. 86–72 ka). It is envisioned that "cold fauna" such as bison and reindeer moved into Britain during stadial MIS 5b (ca. 90 ka) and were subsequently isolated by the rising sea level during MIS 5a. Here we investigate environmental conditions during the Banwell Bone Cave MAZ using bone collagen δ 13 C and δ 15 N and tooth enamel δ 18 O and δ 13 C isotope analysis. We analyse bison and reindeer from the MAZ type-site, Banwell Bone Cave. Our results show unusually high δ 15 N values, which we ascribe to arid conditions within a temperate environment. Palaeotemperature estimates derived from enamel δ 18 O indicate warm temperatures, similar to present day. These results confirm that the Banwell Bone Cave MAZ relates to a temperate interstadial and supports its correlation to MIS 5a rather than MIS 4.